Cardia Gastric Cancer Is Associated With Increased PIK3CA Amplifications and HER2 Expression Than Noncardia Gastric Cancer According to Lauren Classification - Pai, Shih-Min; Huang, Kuo-Hung; Chen, Ming-Huang; Fang, Wen-Liang; Chao, Yee; Lo, Su-Shun; Li, Anna Fen-Yau; Wu, Chew-Wun; Shyr, Yi-Ming (Frontiers in Oncology, 2021)
Background To date, few reports have investigated genetic alterations and clinicopathological features in cardia and noncardia gastric cancer (GC). Methods In total, 435 GC patients receiving curative surgery were included. The clinicopathological features, recurrence patterns, prognoses and genetic alterations were compared between cardia and noncardia GC patients. Results Among the 435 enrolled patients, 47 (10.8%) had cardia GC. Compared with noncardia GC, cardia GC was associated with more intestinal-type tumors and similar initial recurrence patterns and 5-year overall survival (OS; 50.8% vs. 50.5%, P = 0.480) and disease-free survival (DFS; 48.6% vs. 48.9%, P = 0.392) rates. For both intestinal-type GC and diffuse-type GC, the clinicopathological features and 5-year OS and DFS rates were not significantly different between the cardia and noncardia GC patients. Multivariable analysis showed that cardia GC was not an independent prognostic factor. Compared with noncardia GC, cardia GC was associated with increased PIK3CA amplification than in patients with intestinal-type GC and was associated with increased HER2 expression in patients with diffuse-type GC. Conclusions Cardia GC is not an independent prognostic factor. In cardia GC patients with intestinal-type GC, PIK3CA amplification was more common, and in those with diffuse-type GC, HER2 expression was more common. Targeted therapy may be beneficial for these patient subgroups.